PENGANUTAN ASAS SISTEM DUA JALUR (DOUBLE TRACK SYSTEM) DALAM MELINDUNGI ANAK YANG BERKONFLIK DENGAN HUKUM: TINJAUAN FORMULASI DAN APLIKASINYA - Nasriana, Nasriana (Nurani, 2015)
Abstract: Overview of the sanctions measures, especially in thecontext of a criminal measure as a reflection of the adoption of adouble track system in Act No. 11 of 2012 turned out to be verysimple and consequently weakening back the adoption of thisprinciple. This shows that there are doubts the legislators informulating sanctions act as an alternative to criminalsanctions for children in conflict with the law and ultimatelythe adoption of a double track system becomes less meaningful.ملخص: نظرة عامة على صیاغة تدابیر الجزاءات ، وخاصة في سیاق إجراء جنائيبوصفھا انعكاسا لاعتماد نظام المسار المزدوج في القانون رقم أحد عشر من 2012تبین أن تكون بسیطة جدا و بالتالي یضعف مرة أخرى اعتماد من ھذا المبدأ. ھذا یدلعلى أن ھناك شكوك المشرعین في صیاغة عقوبات یكون بمثابة بدیل ل عقوباتجنائیة على الأطفال في نزاع مع القانون ، وفي نھایة المطاف اعتماد نظام المسارالمزدوج یصبح أقل وضوحا.Kata Kunci: anak bermasalah dengan hukum